2018
DOI: 10.17576/gema-2018-1801-01
|View full text |Cite
|
Sign up to set email alerts
|

Thai Learners’ Acquisition of L2 Collocations: An Interlanguage Perspective

Abstract: The emergence of second language (L2) collocation studies has grabbed the attention of a number of scholars. However, few empirical studies from an interlanguage perspective have addressed the issue of how learners acquire L2 collocations. The current study investigated what grammatical and lexical collocations posed difficulty to Thai EFL learners and whether learners of different proficiency levels exhibited the same order of acquisition. The study also attempted to explore whether task differences significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Vocabulary learning is a key to second language (L2) acquisition. Out of all lexical items, synonyms often prove to be challenging for learners' acquisition of L2 vocabulary (Sridhanyarat, 2018). According to Webb and Nation (2017), a synonym refers to "a word or phrase that has the same meaning as another word or phrase" (p. 284).…”
Section: Introductionmentioning
confidence: 99%
“…Vocabulary learning is a key to second language (L2) acquisition. Out of all lexical items, synonyms often prove to be challenging for learners' acquisition of L2 vocabulary (Sridhanyarat, 2018). According to Webb and Nation (2017), a synonym refers to "a word or phrase that has the same meaning as another word or phrase" (p. 284).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a limited number of studies on Thai EFL learners' receptive vocabulary knowledge. Recently, Sridhanyarat (2018) investigated Thai learners' acquisition of L2 collocations between high and low proficiency levels. By using receptive and productive tasks, the study found that regardless of the proficiency levels, all the learners had difficulties to identify all the target collocations; yet verb-preposition collocations seem to be identifiable for advanced learners.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a study by Mohajeri et al (2013) on the difficulty level of the two kinds of collocations, learners found grammatical collocations to be more difficult than lexical ones, indicating noun-preposition as the hardest collocation. In Thailand, advanced and elementary learners' knowledge and use of collocations have been recently found to be influenced by L1 transfer, prior knowledge, and familiarity with the given tests (Sridhanyarat, 2018).…”
Section: Collocationsmentioning
confidence: 99%
“…Pembelajaran kosa kata adalah bagian krusial untuk penguasaan bahasa kedua. Dari semua item leksikal, sinonim sering terbukti menjadi tantangan bagi pelajar bahasa kedua (Sridhanyarat, 2018). Banyak kata yang memiliki Sinonim sebagai salah satu bagian penting dalam kajian kosa kata secara lazim yang diartikan sebagai kata-kata yang mempunyai makna semantis yang sama.…”
Section: Pendahuluanunclassified